2010
DOI: 10.3233/jad-2010-1223
|View full text |Cite
|
Sign up to set email alerts
|

Grey and White Matter Changes at Different Stages of Alzheimer's Disease

Abstract: This study investigates abnormalities of grey (GM) and white matter (WM) in Alzheimer's disease (AD), by modeling the AD pathological process as a continuous course between normal aging and fully developed dementia, with amnesic mild cognitive impairment (aMCI) as an intermediate stage. All subjects (9 AD, 16 aMCI patients, and 13 healthy controls) underwent a full neuropsychological assessment and an MRI examination at 3 Tesla, including a volumetric scan and diffusion tensor (DT)-MRI. The volumes were proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
94
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 51 publications
15
94
1
2
Order By: Relevance
“…Additionally, the ROI analysis revealed significant alterations in FA in the body and splenium of the corpus callosum, as well as the right superior longitudinal fasciculus. Previous studies that have assessed cross-sectional differences in FA between Alzheimer's disease and healthy controls have consistently revealed decreases in FA in the corpus callosum, SLF, and cingulum [32][33][34][35][36][37] -which agrees with our findings. The longitudinal alterations in these diffusion metrics are consistent with previous work done that identified FA and MD changes in the genu and body of the corpus callosum, fornix, and left cingulum over a 12-month follow-up DTI study, 8 highlighting that these regions are still vulnerable to change even in progressive mild-moderate Alzheimer's disease.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, the ROI analysis revealed significant alterations in FA in the body and splenium of the corpus callosum, as well as the right superior longitudinal fasciculus. Previous studies that have assessed cross-sectional differences in FA between Alzheimer's disease and healthy controls have consistently revealed decreases in FA in the corpus callosum, SLF, and cingulum [32][33][34][35][36][37] -which agrees with our findings. The longitudinal alterations in these diffusion metrics are consistent with previous work done that identified FA and MD changes in the genu and body of the corpus callosum, fornix, and left cingulum over a 12-month follow-up DTI study, 8 highlighting that these regions are still vulnerable to change even in progressive mild-moderate Alzheimer's disease.…”
Section: Discussionsupporting
confidence: 83%
“…Despite its precise anatomical-functional localization being still under debate [24,25,41,44,45], constructional apraxia is generally observed in patients with parietal [39] or frontal lobe [23] damages. For example, in a previous volumetric study we found grey matter atrophy restricted in the parietal, occipital and temporal brain areas of patients with AD and evidence of constructional apraxia [4]. The present study suggested a direct involvement of the FAT in different aspects of constructional apraxia abilities as measured by Copy of drawings tasks and by Raven's Coloured Matrices.…”
Section: Discussionmentioning
confidence: 60%
“…In its typical form, AD presents with a distinct pattern of grey (GM) and white matter (WM) brain tissue damage [2], supporting the existence of a disconnection syndrome [2,3] in addition to regional GM loss. Several previous studies used diffusion tensor imaging (DTI) to investigate the role of structural brain disconnection in AD at different clinical stages [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genu has a lower AF compared to the splenium. Several major white matter fibre bundles, including those connecting to the hippocampal structures, pass through the genu of the CC (Serra et al, 2010). Anatomical localization of AF reductions in amnestic MCI (aMCI) seems to be a robust finding across a variety of approaches.…”
Section: Diffusion Tensor Imaging (Dti)mentioning
confidence: 99%